Konsep Pendidikan anak dalam Al-Qur’an dan Hadits Sebagai Landasan yang Kokoh dalam Membentuk Insan Kamil - Mir’atul Farikhah; Muhammad Hori (Ar-rayyan: Journal Of Islamic Education, 2024)
Islamic child education is deeply rooted in the Qur'an and Hadith, extending beyond the mere transfer of knowledge. The concept of Islamic education aims to cultivate insan kamil, a complete individual who possesses a balance of faith, knowledge, and righteous deeds. The Qur'an explicitly commands parents to educate their children, both formally and informally. The Hadith of the Prophet Muhammad SAW also provides detailed guidance on the methods and materials of education suitable for children's natural inclinations. This research will delve deeper into the objectives of child education from an Islamic perspective, by analyzing relevant verses of the Qur'an and Hadith. Furthermore, this study will compare the objectives of Islamic education with those of modern education to identify similarities and differences. This research also employs a library research method, with data collected from books, journals, and other supporting documents.